A study of organizational attitude towards risk and its impact on crisis preparedness among Malaysian manufacturers / Hayati Mohd Dahan - Dahan, Hayati Mohd (Universiti Teknologi MARA Cawangan Pahang, 2007)
The organizational crisis preparedness includes three components, namely signal detection, prevention and recovery mechanism. Based on the Protection and Motivation Theory (Maddux & Rogers, 1983), a study was conducted among Malaysian manufacturing organizations listed in the Federation Malaysian Manufacturing Directory, 2003. Regression analyses on a sample of 106 organizations showed that organizational perception of risk was negatively correlated with organizational crisis preparedness. Findings and implications for managerial practice are discussed.